2018
DOI: 10.1159/000492619
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphodiesterase Inhibitor Pentoxifylline as a Novel Adjunct to Antidepressants in Major Depressive Disorder Patients: A Proof-of-Concept, Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Background: There is evidence for an association between major depressive disorder (MDD) and both inflammatory and phosphodiesterase (PDE) pathways. This study aimed to evaluate the adjunct role of the PDE inhibitor pentoxifylline (PTX), a compound with anti-inflammatory properties, in the treatment of adult patients with MDD. Methods: This was a prospective, 12-week, double-blind study of parallel groups. Eighty adult outpatients who met the DSM-IV criteria for MDD participated in the trial. Patients were req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 44 publications
6
39
0
Order By: Relevance
“… 12 , 31 , 33 Regarding the response and remission rates in the placebo group, which were 65% and 50%, they were also comparable to the previously reported response and remission rates for monotherapy in two published studies, which were 58%–76%, and 27%–64%, respectively. 12 , 34 , 35…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“… 12 , 31 , 33 Regarding the response and remission rates in the placebo group, which were 65% and 50%, they were also comparable to the previously reported response and remission rates for monotherapy in two published studies, which were 58%–76%, and 27%–64%, respectively. 12 , 34 , 35…”
Section: Discussionsupporting
confidence: 88%
“…It has been reported that using combined medications at the beginning of the treatment of MDD patients may provide additional therapeutic benefits as ~50% of the patients do not respond to the first‐line antidepressants. 2 , 3 Although study designs make direct comparison a difficult issue, the response rate of 90% in the CLS combination group is consistent to that of previous studies (89%–92%) including simvastatin, 31 metformin, 32 or pentoxifylline 12 as adjuvant therapies in MDD patients over 6 and 12 weeks. Furthermore, the remission rate of 80% in our study is also consistent with the 59%–85% remission rates in the above‐mentioned trials.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Furthermore, inflammatory cytokines may influence astrocytes, leading to a reduction in glutamate reuptake and increase in its release, together with a decrease in the synthesis of brain-derived neurotrophic factor (BDNF), which has an impact on neuronal integrity and neurogenesis [7]. Recent clinical studies have demonstrated that patients with MDD have elevated serum levels of pro-inflammatory cytokines, including tumor necrosis factor alpha (TNF-α) and interleukins IL-1b and IL-6 [8,9]. The results of these studies showed an improvement in mood and enhanced antidepressant response as a result of the suppression of cytokine signaling in MDD patients [10].…”
Section: Introductionmentioning
confidence: 99%